Atrasentan: a novel and rationally designed therapeutic alternative in the management of cancer. Issue 3 (June 2005) - Jimeno, Antonio; Carducci, Michael
Endothelin axis deregulation triggers a series of events that ultimately activate proliferation, invasion, escape from programmed cell death, new vessel formation, abnormal osteogenesis and alteration of nociceptive stimuli. Atrasentan is a novel agent that effectively targets this pathway and is able to inhibit and/or reverse several of those events. Biologic and clinical activity in patients with prostate cancer has been demonstrated in a Phase III, placebo-controlled setting by the suppression of markers of biochemical prostate cancer progression and a delay in time to disease progression. Atrasentan represents a new therapeutic option in the management of prostate cancer, especially in those patients with bone metastases. However, its precise role in other diseases such as ovarian cancer is yet to be defined.